Electro‐Thermal model of thermal breakdown in multilayered dielectric elastomers. Issue 2 (13th December 2018) - Christensen, Line R.; Hassager, Ole; Skov, Anne L.
Abstract : Energy transduction of dielectric elastomers involves minute electrical and mechanical losses, both of which potentially increase the temperature within the elastomer. Thermal breakdown of dielectric elastomers occur when heat generated therein cannot be balanced by heat loss on the surface, which is more likely to occur in stacked dielectric elastomers. In this article an electro‐thermal model of a multilayered dielectric elastomer able to predict the possible number of layers in a stack before thermal breakdown occurs is presented. Simulation results show that point of breakdown is greatly affected by an increase in surrounding temperature and applied electric field. Furthermore, if the stack diameter is large, thermal insulation of the cylindrical surface is a valid approximation. Two different expressions for the electrical conductivity are used, and it is concluded that the Frank‐Kamenetskii expression is more conservative in prediction of point of breakdown than the Arrhenius expression, except at high surrounding temperature. © 2018 American Institute of Chemical Engineers AIChE J, 65: 859–864, 2019